Preparation method and application of phosphate / magnesium oxide composite modified charcoal
Through the preparation method of phosphate/magnesium oxide composite modified biochar, the problem of small improvement in the modification performance of biochar in the prior art is solved, efficient adsorption of heavy metal-contaminated wastewater is achieved, and the adsorption efficiency of biochar is significantly improved.
Patent Information
- Application Number
- CN202411826712.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-01
AI Technical Summary
The existing biochar modification methods have problems such as pore size collapse and blockage and performance improvement, and it is difficult to effectively improve the adsorption capacity of biochar to heavy metal-contaminated wastewater.
The preparation method of phosphate/magnesium oxide composite modified biochar is adopted, and polar groups and mineral components are introduced through impregnation-pyrolysis method to generate phosphorus-magnesium complexes, thereby improving the functional group content and ion exchange ability of biochar.
The adsorption efficiency of biochar is significantly improved, and the maximum adsorption capacity of Cu(II)/Cd(II) reaches 190.74 mg/g and 284.50 mg/g, respectively, and the efficient adsorption capacity is maintained within a wide pH range.
Smart Images

Figure CN119733479A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization, relates to biochar modification, and specifically to a preparation method and application of phosphate / magnesium oxide composite modified biochar. Background Art
[0002] With the rapid development of industries such as mining, electroplating, leather processing, and alloy manufacturing, the problem of heavy metal pollution in water bodies is becoming increasingly serious. It is crucial to develop efficient and low-cost heavy metal contaminated wastewater treatment technology. As an environmentally friendly and efficient emerging heavy metal adsorbent, biochar has achieved satisfactory treatment results in actual wastewater treatment. However, due to the complexity of the polluted environment and the diversity of heavy metals, the porous structure, cation exchange capacity, surface charge, and functional groups of biochar limit its ability to adsorb heavy metal ions. In order to improve the adsorption efficiency of biochar and meet the needs of treating heavy metal pollution in water bodies, biochar needs to be modified. Common methods include chemical modification and physical modification. Chemical modification is the most widely used method, mainly including acid modification, alkali modification, oxidant modification, and metal salt or metal oxide modification.
[0003] Acid modification includes nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid and citric acid modification. Acid washing can increase the richness of functional groups on the surface of biochar, such as COC, C=O, etc., and improve the specific surface area and pore structure of biochar. However, for some biochar, acid modification may reduce its specific surface area. For example, after straw biochar was treated with 2% sulfuric acid, its specific surface area increased from 71.35m 2 / g dropped to 56.9m 2 / g.
[0004] Alkali modification is the use of Class I metal hydroxides (KOH or NaOH) to activate biochar, which improves adsorption performance by increasing porosity and specific surface area and producing more oxygen-containing functional groups on the biochar surface. Alkali modification increases the specific surface area and oxygen-containing functional groups of biochar, while increasing the positive charge on the biochar surface, which is not conducive to the adsorption of positively charged heavy metal ions. Feng et al. prepared a series of alkali-modified biochars using KOH and found that alkali modification increased the hydrophobicity of biochar, making the material unfavorable for water pollution control.
[0005] Oxidant modification can increase the content of oxygen-containing functional groups on biochar, but the type and concentration of the oxidant must be selected in combination with the characteristics of the target pollutant. The study by Huff et al. showed that when the H2O2 content increased, the adsorption capacity of modified biochar for methylene blue gradually decreased, and the adsorption capacity of biochar for pollutants changed with the change of oxidant concentration. In addition, the cost of oxidants is relatively high, and harmless treatment after the reaction needs to be considered.
[0006] The modification of metal salts or metal oxides is accomplished in two ways: 1. Mixing metal salts or metal oxides with raw materials and then pyrolyzing them to synthesize biochar; 2. First, pyrolyzing the raw materials to obtain biochar, and then impregnating the biochar with metal salts or metal oxides under certain conditions. Common metals include iron, magnesium, aluminum, and manganese. For example, when biochar is difficult to recover from the water body after removing pollutants from wastewater, the use of iron salts or metal iron oxides to modify the biochar to obtain magnetic properties can solve the recycling problem; however, some metal ions may be released into the water, causing pollution.
[0007] Acid modification may reduce the specific surface area of biochar. Alkaline modification is not conducive to the adsorption of positively charged heavy metal ions by biochar, and increases the hydrophobicity of biochar, making the material unfavorable for the treatment of water pollution. The type and concentration of oxidant modification must be selected in combination with the characteristics of the target pollutants. The adsorption capacity of biochar for pollutants changes with the concentration of the oxidant; and the cost of the oxidant is high, and harmless treatment after the reaction needs to be considered. Modification of metal salts or metal oxides may release some metal ions into the water, causing pollution. Summary of the invention
[0008] In view of the problems that a single modification method may cause pore collapse and blockage, and little performance improvement, the purpose of the present invention is to provide a preparation method and application of phosphate / magnesium oxide composite modified biochar. The composite modification of phosphate / magnesium oxide can achieve complementary advantages and play an important role in improving the polar groups, mineral components and cation exchange capacity of biochar; it solves the problems existing in the above-mentioned prior art and at the same time improves the ability of the modified biochar to treat water pollution problems.
[0009] The present invention is achieved by adopting the following technical solutions: A method for preparing phosphate / magnesium oxide composite modified biochar comprises the following steps: Step 1, preparation of phosphate-modified biochar: taking corn straw powder and placing it in potassium dihydrogen phosphate solution to form a P-impregnated biomass raw material; then drying the P-impregnated biomass raw material; placing the dried P-impregnated biomass raw material into a muffle furnace, evacuating to below -0.06Mpa, heating from room temperature to 800°C and maintaining a constant temperature for 2h; cooling to room temperature and taking out the sample for storage to obtain base biochar PBC; Step 2, preparation of phosphate / magnesium oxide composite modified biochar: take the base biochar PBC and add it to the MgCl2 solution and stir, then heat it to 85°C, then add Na2CO3 solution (to form easily decomposable compounds with MgCl2), and heat it in a water bath at 600rpm for 3h, then wash the obtained precursor with ultrapure water until the pH is constant, and dry it; then put the dried precursor into the muffle furnace, evacuate it to below -0.06Mpa, and keep the temperature constant at 800°C from the starting temperature to 2h; after cooling to room temperature, take out the sample for storage, and the modified biochar with PBC as the base material is named MgO-PBC.
[0010] Further preferably, in step 1: the corn stalk powder is passed through 60 mesh; the concentration of the potassium dihydrogen phosphate solution is 0.36 mol / L, and the 60 mesh corn stalk powder and the potassium dihydrogen phosphate solution are mixed at a ratio of 1:10 (m:V), that is, each gram of 60 mesh corn stalk powder is mixed with 10 mL of potassium dihydrogen phosphate solution; after mixing evenly, the mixture is heated in an 85°C water bath at a speed of 600 rpm for 6 hours. The drying temperature is 85°C and the time is 12 hours.
[0011] Further preferably, in step 2: the mass ratio of the base biochar PBC to the amount of Mg is 1:0.24. That is, 5 g of the base biochar PBC is added to 50 mL of 1.0 mol / L MgCl2 solution; 50 mL of 1.0 mol / L Na2CO3 solution is added; the drying temperature is 85°C and the time is 24 hours; the modified biochar with PBC as the base material is named 5-MgO-PBC.
[0012] Further preferably, in both step 1 and step 2, the temperature is increased to 800° C. at a heating rate of 10° C. / min.
[0013] The phosphate / magnesium oxide composite modified biochar prepared by the method of the present invention can be used for adsorption of heavy metal Cu / Cd polluted wastewater. The initial pH of heavy metal Cu / Cd polluted wastewater is ≥3; the dosage of phosphate / magnesium oxide composite modified biochar is 1g / L, the adsorption time is more than 10h, and Cu 2+ The concentration is 5~100mg / L, Cd 2+ The concentration is 100-200 mg / L.
[0014] The present invention uses an impregnation-pyrolysis method to prepare a phosphate / magnesium oxide composite modified biochar 5-MgO-PBC, successfully introduces polar groups and mineral components into the biochar matrix, generates phosphorus-magnesium complexes on the surface of the biochar, and improves the functional group content and ion exchange capacity of the biochar. Based on static adsorption research and mechanism exploration, the effects of factors such as influent flow rate and bed height on the dynamic adsorption efficiency of 5-MgO-PBC during industrial treatment of heavy metal-contaminated wastewater are studied through a fixed bed adsorption column, providing data support and technical support for the industrial treatment of heavy metal-contaminated wastewater by 5-MgO-PBC.
[0015] The present invention uses corn stalks as biomass raw materials, and prepares phosphate / magnesium oxide composite modified biochar by impregnation-co-pyrolysis. The static adsorption efficiency of 5-MgO-PBC for heavy metals Cu(Ⅱ) / Cd(Ⅱ) is explored by influencing factors such as the initial pH value of the solution, the coexisting ionic strength, and the adsorbent dosage. 5-MgO-PBC is characterized and analyzed by BET, SEM-EDS, FT-IR, XRD, XPS, and other methods. The adsorption kinetics and adsorption isotherm model of 5-MgO-PBC are combined to analyze the adsorption performance of 5-MgO-PBC. The fitting results of BC adsorption of Cu(Ⅱ) / Cd(Ⅱ) were analyzed to analyze the possible mechanism of action of modified biochar adsorption of heavy metal Cu(Ⅱ) / Cd(Ⅱ); 5-MgO-PBC was loaded into a fixed bed adsorption column, and the dynamic adsorption efficiency of the material for heavy metal Cu(Ⅱ) / Cd(Ⅱ) was studied by changing the adsorption parameters such as the bed height and water inlet flow rate of the adsorption column. The dynamic adsorption was fitted with the help of BDST model, Thomas model, etc., and the feasibility of 5-MgO-PBC for industrial treatment of heavy metal contaminated wastewater was analyzed. The technical solution provided by the present invention has the following advantages compared with the prior art: (1) Using the specific surface area of biochar as an indicator, the methods of preparing biochar by hydrothermal synthesis and slow pyrolysis were studied. The optimal biochar preparation method was determined to be: muffle furnace vacuum environment, pyrolysis temperature of 800°C, residence time of 2h. The specific surface area of the prepared base biochar 60BC can reach 434.114m 2 / g. KH2PO4 and metal oxide MgO were modified by different treatment methods, and the modified biochar was selected based on the adsorption research results as the screening criteria, and the optimal modification conditions were obtained: 0.36mol / L KH2PO4 solution was mixed in a ratio of 1:10 (m:V), fully impregnated with 60 mesh corn straw powder and heated in a water bath for 6h, and pyrolyzed in a muffle furnace to prepare the base biochar PBC; 5gPBC was impregnated with 50mL 1.0mol / L MgCl2 solution and Na2CO3 solution, heated in a water bath for 5h, the secondary carbonization temperature was 800℃, and the carbonization time was 2h, to obtain phosphate / magnesium oxide composite modified biochar 5-MgO-PBC. The composition analysis results showed that the H / C molar ratio and O / C molar ratio of 5-MgO-PBC were lower than the limit values of the defined biochar, and its hydrophilicity was stronger than that of the original biochar (60BC). The characterization results of 5-MgO-PBC were analyzed by SEM-EDS, FT-IR, XRD and XPS, which showed that the material exhibited a rich porous structure, and P and MgO were also successfully loaded on the material.
[0016] (2) The results show that 5-MgO-PBC has good static adsorption efficiency for Cu(Ⅱ) / Cd(Ⅱ), and the maximum adsorption capacity can reach 190.74mg / g and 284.50mg / g respectively. The results of the study on the influence of solution chemical properties show that Cu(Ⅱ) / Cd(Ⅱ) in wastewater with pH ≥ 3 can be effectively adsorbed by 5-MgO-PBC, and the coexistence of different cations cannot affect its excellent adsorption efficiency. The regeneration performance study found that after 5 cycles of adsorption, the adsorption efficiency of 5-MgO-PBC for Cu(Ⅱ) / Cd(Ⅱ) decreased by about 20%, which may be due to the partial loss of magnesium in the modified biochar, the partial loss of adsorption sites, and the slight changes in structure and pore blockage during the regeneration process. The pseudo-second-order kinetics and Langmuir model can highly fit the adsorption process of 5-MgO-PBC for the two heavy metal ions, indicating that the adsorption of 5-MgO-PBC for Cu(Ⅱ) / Cd(Ⅱ) belongs to monolayer chemical adsorption. The study of adsorption mechanism showed that surface coprecipitation and ion exchange were the main mechanisms of 5-MgO-PBC adsorption of Cu(Ⅱ). Oxygen-containing functional groups can provide carbonate for some precipitation reactions. The products of surface coprecipitation are mainly copper hydroxide, copper phosphate and basic copper carbonate. The main mechanisms of 5-MgO-PBC adsorption of Cd(Ⅱ) are ion exchange, surface coprecipitation and complexation.
[0017] (3) The results of the dynamic adsorption study of the fixed bed adsorption column show that the increase in bed height can increase the adsorption capacity and wastewater treatment capacity of the fixed bed adsorption column, the low flow rate can improve the dynamic adsorption efficiency, and the increase in influent concentration can shorten the wastewater treatment cycle and improve the dynamic adsorption efficiency. When the bed height is 7 cm, the influent flow rate is 20 mL / min, and the influent Cu(Ⅱ) concentration is 60 mg / L, the dynamic adsorption capacity of 5-MgO-PBC for Cu(Ⅱ) can reach 78.87 mg / g; when the bed height is 5 cm, the influent flow rate is 20 mL / min, and the influent Cd(Ⅱ) concentration is 150 mg / L, the dynamic adsorption rate of 5-MgO-PBC for Cd(Ⅱ) is as high as 88.95%. The Thomas model can accurately analyze and predict the entire dynamic adsorption system, and has a certain guiding role in the industrial treatment of heavy metal-contaminated wastewater by 5-MgO-PBC.
[0018] The invention has reasonable design and good practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0020] Figure 1 Represents the thermogravimetric analysis curve (TG-DTG) of corn stover.
[0021] Figure 2 Comparison of specific surface areas of biochar synthesized by hydrothermal synthesis of straw under different ratios and mesh sizes.
[0022] Figure 3 represents the adsorption efficiency of modified biochar; (a) different types of biochar for Cu 2+ (b) Adsorption of Cu by phosphate / magnesium oxide composite modified biochar 2+ / Cd 2+ adsorption.
[0023] Figure 4 The effect of pH on the adsorption of Cu on 5-MgO-PBC 2+ (a, c) and Cd 2+ The impact of (b, d).
[0024] Figure 5 The biochar addition rate has an effect on Cu 2+ (a) Cd 2+ (b) Effect of adsorption amount and adsorption rate.
[0025] Figure 6 The effect of 5-MgO-PBC on Cu 2+ (a) Cd 2+ (b) Adsorption kinetics.
[0026] Figure 7 Cu adsorption on 60BC (a) and 5-MgO-PBC (b) 2+ and Cd 2+ The adsorption isotherm model.
[0027] Figure 8 The effect of ionic strength on the adsorption of Cu on 5-MgO-PBC 2+ impact.
[0028] Fig. 9 The effect of ionic strength on the adsorption of Cd by 5-MgO-PBC 2+ impact.
[0029] Fig.10 It indicates that 5-MgO-PBC adsorbs Cu 2+ and Cd 2+ After the cycle capacity.
[0030] Fig.11 Represents the SEM-EDS images of 60BC and 5-MgO-PBC; wherein, a: SEM image of 60BC, b: SEM image of 5-MgO-PBC, c, d: SEM-EDS images of 5-MgO-PBC after adsorbing Cu(Ⅱ), e, f: SEM-EDS images of 5-MgO-PBC after adsorbing Cd(Ⅱ).
[0031] Fig.12 Shows the N2 adsorption-desorption isotherm of 5-MgO-PBC.
[0032] Fig.13 FT-IR spectra of 5-MgO-PBC showing the adsorption of different heavy metal ions.
[0033] Fig.14 Shows the X-ray diffraction pattern of 5-MgO-PBC before and after adsorption of heavy metals Cu(Ⅱ) / Cd(Ⅱ).
[0034] Fig.15 This shows the overall XPS spectrum of 5-MgO-PBC before and after the adsorption of Cu(Ⅱ) and Cd(Ⅱ).
[0035] Fig.16 Represents the XPS spectra before and after the adsorption of Cu(Ⅱ); among them, (a) C 1s spectrum before adsorption, (b) C 1s spectrum after the adsorption of Cu(Ⅱ), (c) P 2p spectrum before adsorption, and (d) P 2p spectrum after the adsorption of Cu(Ⅱ).
[0036] Fig.17Represents the XPS spectra before and after the adsorption of Cd(Ⅱ); among them, (a) C 1s spectrum before adsorption, (b) C 1s spectrum after adsorption of Cd(Ⅱ), (c) P 2p spectrum before adsorption, and (d) P 2p spectrum after adsorption of Cd(Ⅱ). DETAILED DESCRIPTION
[0037] In order to more clearly understand the above-mentioned purposes, features and advantages of the present invention, the scheme of the present invention will be further described below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, not all of the embodiments. The specific embodiments of the invention are described in detail below in conjunction with the accompanying drawings.
[0038] 1. Preparation method of biochar 1.1 Preparation of raw biochar (1) Preparation of biomass raw materials: Use agricultural waste corn stalks as biomass raw materials, remove impurities, stir and mix evenly in deionized water, clean the soil particles attached to the surface of the stalks, drain naturally and put them in an oven at 70℃~80℃ for 24h. Then use a crusher to crush them and sieve them to 60 mesh, 80 mesh, 120 mesh and 200 mesh, put them in sealed bags, affix labels and indicate the name and mesh number of the biomass raw materials, and store them for future use.
[0039] (2) Preparation of biochar in hydrothermal reactor: Four biomass raw materials with different mesh sizes were mixed with deionized water in different ratios of 1:4, 1:5, and 1:7 (m:V). At room temperature, they were stirred with a magnetic stirrer at a speed of 200 rpm until they were evenly mixed. The slurry biomass raw materials were transferred to a reactor with a volume of 100 mL (1 / 3 of the space should be left in the reactor), carbonized at 260°C for 2 hours, and then naturally cooled to room temperature. The products were collected and washed with deionized water twice, filtered with a vacuum filter, and then dried in an oven at 80°C for 24 hours. The hydrothermal charcoal (HC) obtained by drying and grinding was named XXHC-Yt, where XX represents the mesh size, HC is the abbreviation of hydrothermal charcoal, Y represents the ratio, and t represents the carbonization time; for example, 60HC-4-2:60 represents 60-mesh corn straw powder, 4 represents the ratio of raw material to water of 1:4, and 2 represents the carbonization time of 2 hours.
[0040] Preparation of biochar in a tubular furnace: Fill a crucible with corn straw powder of different mesh sizes and place it in a tubular furnace. Use a rotary vane vacuum pump to evacuate to vacuum (-0.06Mpa), and heat it to 400℃ or 800℃ at a heating rate of 10℃ / min, and keep it at a constant temperature at 400℃ or 800℃ for 120min of carbonization. When the sample is cooled to room temperature, the biochar obtained by grinding is named GXXBC-T, where G represents the tubular furnace, XX represents the mesh size of the corn straw powder, BC is the abbreviation of biochar, and T represents the carbonization temperature; for example, G60BC-400: 60 represents 60 mesh corn straw powder, and 400 represents the carbonization temperature of 400℃.
[0041] Preparation of biochar in a muffle furnace: Take the sieved corn straw powder and put it into ceramic crucibles of different sizes. Cover the crucible lid and seal it with aluminum foil, and put it into the furnace. Use a rotary vane vacuum pump to evacuate to vacuum (-0.06Mpa). The starting temperature is room temperature, and the temperature is increased to 800℃ at a rate of 10℃ / min, and kept at 800℃ for 2h. After cooling to room temperature, take out the sample, grind it and store it. The obtained biochar is named XXBC, XX represents the mesh number, and BC is the abbreviation of biochar; such as 60BC: 60 represents 60 mesh corn straw powder.
[0042] 1.2 Preparation of phosphate / magnesium oxide composite modified biochar Preparation of phosphorus (P) modified biochar: Weigh a certain amount of 60 mesh corn straw powder and mix it with potassium dihydrogen phosphate solution (KH2PO4) at a ratio of 1:10 (m:V) to fully impregnate the biomass raw material. After mixing evenly, heat it in an 85℃ water bath at 600rpm for 6h. Then, the treated P-impregnated biomass raw material was divided into several culture dishes and dried at 85℃ for 12h. The biochar sample prepared by the same muffle furnace preparation method as the original biochar was recorded as PBC.
[0043] Preparation of magnesium oxide (MgO) modified biochar: 3g and 5g of base biochar (60BC or PBC) were added to 50mL 1.0mol / L MgCl2 solution and stirred for 3h. The Mg content was controlled by changing the amount of biochar. Subsequently, the beaker containing the mixture was placed in a water bath, and the water bath temperature was raised to 85°C. Then 50mL 1.0mol / L Na2CO3 solution (which forms an easily decomposable compound with MgCl2) was added and heated in a water bath for 3h. The resulting precursor was washed with ultrapure water until the pH was constant and dried at 85°C for 24h. Subsequently, different precursors were prepared into modified biochar by muffle furnace pyrolysis. The modified biochar with 60BC as the base material was named Z-MgO-BC; the modified biochar with PBC as the base material was named Z-MgO-PBC; Z represents the amount of base biochar, and the amount of Mg is 1.2g (0.05mol*24g / mol=1.2g), for example, the percentage of Mg in 3-MgO-PBC relative to PBC is 40%, and the percentage of Mg in 5-MgO-PBC relative to PBC is 24%).
[0044] 2. Characterization methods and adsorption efficiency of biochar 2.1 Thermogravimetric analysis In order to explore the reaction of corn straw during pyrolysis, a thermogravimetric analyzer was used to test it. The mass loss and composition changes of corn straw with temperature changes during the entire pyrolysis process were analyzed, and the optimal pyrolysis temperature of corn straw was mastered. Test method: Weigh 25 mg of 60-mesh corn straw powder, the temperature range is 30℃~900℃, the nitrogen flow rate is 100mL / min, the heating rate is 10℃ / min, and the analysis is performed on the thermogravimetric analyzer to obtain the heating curve.
[0045] like Figure 1 As shown in the figure, the pyrolysis process of corn straw is divided into three stages. The first stage is the volatilization stage of straw moisture at 30℃~130.3℃. The mass loss (TG) curve shows a partial decrease, but the weight loss is not significant. Because the 60-mesh corn straw powder undergoes a drying step before pyrolysis, the weight loss is only 2.3%. The second stage 130.3℃~400℃ is the decomposition stage of cellulose, hemicellulose and lignin. Hemicellulose is mainly decomposed at 130.3℃~205℃, which is the most unstable substance in the straw; cellulose is mainly decomposed at 205℃~260℃; lignin is mainly decomposed in the range of 260℃~400℃. Lignin has a wide decomposition range, and sometimes the decomposition temperature can reach 900℃, so it is the most difficult component to decompose. The comprehensive pyrolysis and carbonization stage is 400℃~900℃, especially at 806.9℃, there are deep residues decomposing, including the decomposition of part of lignin. Overall, the biochar prepared by pyrolysis at 800℃ is completely decomposed and has a stable structure.
[0046] The biochar material prepared in the embodiment of the present invention is used to adsorb heavy metal ions in wastewater. In order to avoid long-term immersion in water, which may lead to decomposition or strength reduction, fully pyrolyzing the biomass raw material is the top priority in preparing biochar. When the pyrolysis temperature is high, the corn stalks are completely pyrolyzed and carbonized, and the structural stability is strong. Therefore, the pyrolysis temperature is selected at 800°C after comprehensive consideration.
[0047] 2.2 Component Analysis The composition analysis of biochar materials is carried out by using the CHN mode and O mode of the organic element analyzer (EA) to analyze the contents of C, H, O, and N. Composition analysis can be used to determine the relevant properties of the material. For example, the O / C molar ratio can determine the hydrophilicity and hydrophobicity of biochar; the H / C and O / C molar ratios can determine whether a pyrolyzed biomass can be considered as biochar. Analysis principle: In order to clarify the content and proportion of each element in the material, the ground biochar is placed in an aluminum capsule, which is then converted into volatile substances through high-temperature cracking after entering the oxygen column. The concentration is detected by a thermal conductivity cell to calculate the content of each element.
[0048] The composition of 60BC and 5-MgO-PBC was analyzed to explore the original properties of biochar and the effect of modified adsorption of heavy metals Cu(Ⅱ) / Cd(Ⅱ). According to the test results, compared with 60BC, the C content of 5-MgO-PBC decreased (9.08%), the O content increased by 3.50%, and the N content increased by only 0.05%; this is related to the modification of phosphate / magnesium oxide. The increase in the O content in 5-MgO-PBC indicates that the composite modification of phosphate / magnesium oxide enriched the oxygen-containing functional groups on its surface and increased the types and number of oxygen-containing functional groups. The International Biochar Initiative (IBI) and the European Biochar Certificate (EBC) Guidelines state that a pyrolyzed biomass can be considered as biochar only when the H / C molar ratio is less than 0.7 and the O / C molar ratio is less than 0.4. In the examples of the present invention, the H / C molar ratio and O / C molar ratio of 60BC and 5-MgO-PBC are both lower than the limit value for defining biochar, that is, both are biochar. The hydrophilicity and hydrophobicity of biochar are usually related to the number of polar groups on its surface, and the O / C molar ratio is considered to be an indicator of the richness of polar functional groups in biochar. The O / C molar ratio of 5-MgO-PBC increased by 0.059, indicating that 5-MgO-PBC has stronger hydrophilicity.
[0049] 2.3 Specific surface area analysis The specific surface area of the biochar was obtained by testing and analyzing with a specific surface area pore size analyzer. The test steps were as follows: the ground biochar was vacuum calcined at 120°C for 12 hours and placed in a liquid nitrogen tank for N2 adsorption-desorption test.
[0050] In order to quantitatively analyze the variation of specific surface area of biochar prepared under different conditions, the embodiment of the present invention uses N2 adsorption-desorption test to test and analyze the specific surface area of different biochars. Figure 2 As shown in the figure, in the hydrothermal synthesis method, as the decarboxylation reaction of cellulose and hemicellulose proceeds, a large amount of gas generated is discharged through the pores, the pore structure is developed, and the specific surface area of biochar is increased. Figure 2 (a) As the ratio increases, the specific surface area of biochar gradually decreases. The specific surface area of 60HC-4-2 is 3.971 m 2 / g, the specific surface areas of 60HC-5-2 and 60HC-7-2 were reduced to 3.547 m 2 / g and 2.84m 2 / g, indicating that the structural changes of hydrates are mainly manifested in the shrinkage and collapse of pore structure. Figure 2 (b) As shown in Figure 2, when the hydrothermal carbonization time exceeds 2 h, the pore structure generated in the early stage begins to shrink as time increases, resulting in a decrease in the specific surface area.
[0051] Compared with hydrothermal synthesis, the temperature of slow pyrolysis has a dominant effect on the microstructure and surface properties of biochar, which will affect the feasibility and performance of biochar in specific applications. As the pyrolysis temperature increases, the volatilization and decomposition of solid biomass usually give the biochar a larger specific surface area and pore size. In addition to temperature, the residence time of slow pyrolysis will also affect the specific surface area of biochar. Generally speaking, at a certain temperature, the extension of the residence time will lead to a further increase in the specific surface area. However, compared with increasing the pyrolysis temperature, the effect of residence time on increasing the specific surface area of biochar is not obvious. Therefore, in the embodiment of the present invention, the pyrolysis temperature is increased while the residence time remains unchanged, and two different pyrolysis devices (tube furnace and muffle furnace) are selected. The specific surface area of the biochar prepared by the tube furnace at different temperatures in the same device is quite different. The specific surface area of G60BC-400 is only 8.631m 2 / g, and the specific surface area of G60BC-800 is as high as 50.688m 2 / g. It can be seen that under the same conditions, the fineness of the biomass raw materials will have a slight effect on the specific surface area of the biochar. Under the same conditions, different devices, the specific surface area of the biochar prepared by the tubular furnace is only 50.688m 2 / g, while the specific surface area of biochar (60BC) prepared by muffle furnace can be greatly increased to 434.114m 2 / g. Therefore, the subsequent preparation of biochar adopts muffle furnace pyrolysis.
[0052] 2.4 Adsorption efficiency of biochar Common Cu in wastewater from semiconductor and battery industries 2+ The concentration is 5~100mg / L, Cd2+ The concentration is 100-200 mg / L. The embodiment of the present invention is suitable for the treatment of wastewater in the actual electronics industry. Cu 2+ The concentration is 60mg / L, Cd 2+ The concentration was 150 mg / L. At room temperature, the same mass of each biochar was put into a conical flask containing Cu(Ⅱ) / Cd(Ⅱ) solution and adsorbed on a desktop constant temperature shaker at 200 rpm for 24 h to explore the adsorption capacity of different biochar materials.
[0053] like Figure 3 As shown in the figure, the ability of the original biochar (60BC) to adsorb heavy metal ions is improved after modification, but the adsorption capacity is different due to different modification methods. Figure 3 (a) shows that the biochar prepared in this example has a certain removal ability for Cu(Ⅱ). The removal rate of Cu(Ⅱ) by 3-MgO-PBC and 5-MgO-PBC during the adsorption process is nearly 100%, while Figure 3 (b) It can be seen that 5-MgO-PBC has a good removal ability for Cu(Ⅱ) / Cd(Ⅱ). Therefore, considering the efficiency, economy and applicability, 5-MgO-PBC was selected as the adsorbent for the adsorption efficiency of Cu(Ⅱ) / Cd(Ⅱ) in this example.
[0054] 2.5. The present invention uses thermogravimetric analysis and component analysis to study the pyrolysis reaction of corn stalks and the composition of biochar. The specific surface area of biochar and the adsorption efficiency of modified biochar are used as test indicators to conduct relevant research on hydrothermal synthesis, slow pyrolysis preparation of biochar, phosphorus modification, magnesium oxide modification, and phosphorus and magnesium oxide composite modification of biochar, and determine that phosphate and magnesium oxide composite modification and muffle furnace pyrolysis are the best modification methods for biochar.
[0055] (1) Thermogravimetric analysis of the biomass raw material corn stalks showed that carbonization can be achieved at a pyrolysis temperature of ≥400°C. However, the biochar prepared at a low pyrolysis temperature has poor structural stability and a small specific surface area. The use of biochar in wastewater requires sufficient pyrolysis, strong stability and a large specific surface area. A comprehensive analysis showed that the pyrolysis temperature was selected to be 800°C. Component analysis showed that the modified 5-MgO-PBC has a stronger hydrophilicity and is suitable for treating heavy metal-contaminated wastewater.
[0056] (2) In the biochar preparation process, 60-mesh corn straw powder was used and heated to 800°C at a rate of 10°C / min in a muffle furnace vacuum environment for 120 min. The prepared corn straw biochar (60BC) had the largest specific surface area (434.114 m 2 / g). The PBC obtained by phosphate impregnation of 60-mesh corn straw powder and muffle furnace pyrolysis was used as the base biochar, and 5g of the base biochar was used for MgO modification. After secondary carbonization, the final modified biochar 5-MgO-PBC was obtained. The adsorption study results showed that 5-MgO-PBC had the best adsorption efficiency for Cu(Ⅱ) / Cd(Ⅱ) among the modified biochars.
[0057] Therefore, a high specific surface area biochar was successfully prepared using a muffle furnace, and its specific surface area was increased from 3.976 m 2 / g increased to 434.114m 2 / g; The composite modification of phosphate and magnesium oxide improves the adsorption efficiency of biochar and increases the utilization space of biochar, which has far-reaching significance for the resource utilization of biochar.
[0058] 3. Static adsorption efficiency of Cu(Ⅱ) / Cd(Ⅱ) on MgO-PBC Through the results of adsorption research and biochar specific surface area analysis, it was learned that 5-MgO-PBC modified biochar was selected for subsequent research; the adsorption capacity of modified biochar is not only affected by the chemical properties, but also has a certain relationship with the adsorption conditions. In order to further explore the effect of changes in water chemical properties on the static adsorption efficiency of modified biochar 5-MgO-PBC, the efficiency of 5-MgO-PBC in static adsorption of heavy metals Cu(Ⅱ) / Cd(Ⅱ) was explored through the influencing factors such as the initial pH value of the solution, the strength of coexisting cations and the amount of adsorbent added. The adsorption kinetics and adsorption isotherm characteristics of 5-MgO-PBC on Cu(Ⅱ) / Cd(Ⅱ) were investigated to confirm the type of its adsorption process. 3.1 Effect of initial pH value on biochar adsorption efficiency Take 25mL of 60mg / L Cu 2+ The solution was placed in a 150 mL conical flask, and the pH value was adjusted using 0.1 mol / L HCl and NaOH solutions. The initial pH value was adjusted to 2-6, and three parallels were set for each pH value. Weigh (0.0250 ± 0.0005) g of biochar and add it to the conical flask. The adsorption reaction lasted for 10 h at room temperature and a shaking speed of 200 rpm. The same adsorption conditions were used to adsorb Cd 2+ The difference is that Cd 2+ The concentration of the solution is 150 mg / L.
[0059] The initial pH value of the solution affects the surface charge of biochar and the ionic form of heavy metals. The effect of pH on the adsorption of Cu(Ⅱ) / Cd(Ⅱ) by 5-MgO-PBC is shown in Figure 2. Figure 4 As shown by Figure 4As can be seen from (a) and (c), the adsorption of Cu(Ⅱ) by 5-MgO-PBC was not affected within the pH range of 3.0 to 6.0. However, as the pH value of the solution decreased, the H + As the concentration increases, the adsorption efficiency of 5-MgO-PBC for Cu(Ⅱ) decreases. When pH=2.0, the adsorption amount of Cu(Ⅱ) is as low as 31.96 mg / g. This phenomenon is consistent with the change of the adsorption amount of heavy metal ions in magnesium-modified biochar due to the effect of pH. When pH≥3, the removal rate is stable at about 99%, indicating that 5-MgO-PBC can effectively remove Cu(Ⅱ) in a wide pH range. The MgO groups on the surface of the modified biochar react with H in a strong acid environment. + The reaction played a certain buffering role. At the same time, 5-MgO-PBC underwent hydrolysis and ion exchange reactions during the removal of Cu(Ⅱ). As the pH value of the solution increased, H + The concentration decreases, because the carboxyl and hydroxyl functional groups on the surface of modified biochar are negatively charged, Cu 2+ With positive charge, electrostatic attraction is generated between the two, which increases the ability of modified biochar to adsorb heavy metal ions.
[0060] In the above reaction, if the pH value is too low, that is, the solution is in a highly acidic state, a large amount of H + The equilibrium of the hydrolysis reaction shifts to the left, or H + The increase in the amount of promotes the buffer reaction, which is not conducive to the adsorption of Cu(Ⅱ). If the solution is so acidic that the effect of the buffer group is negligible, the ion exchange and hydrolysis reaction of Cu(Ⅱ) in the whole system will disappear, and the efficiency of 5-MgO-PBC in adsorbing Cu(Ⅱ) will also decrease.
[0061] Compared with Cu(Ⅱ), the initial pH value of the solution has a greater influence on the adsorption of Cd(Ⅱ) by 5-MgO-PBC. Figure 4 (b) and (d) show that when the pH value is between 4 and 6, the adsorption amount (150 mg / g) and adsorption rate (99%) of Cd(Ⅱ) remain basically unchanged. As the acidity of the solution increases, the efficiency of 5-MgO-PBC in adsorbing Cd(Ⅱ) decreases. When pH=2, the adsorption amount is less than 60 mg / g and the adsorption rate drops to about 40%. This result shows that the initial pH value of the solution has a certain influence on the adsorption of heavy metal ions by 5-MgO-PBC. If the acidity is too high, a large amount of H + Reacts with MgO, affecting the hydrolysis of heavy metal ions and the reaction with Mg 2+ The ion exchange reaction will affect the adsorption efficiency of 5-MgO-PBC. At the same time, competition will also occur in the environment of lower pH value. 2+ and Cd 2+ They are both cationic heavy metals, H+ Higher concentrations may be related to Cu 2+ and Cd 2+ Competing for some adsorption sites on 5-MgO-PBC will also affect the adsorption efficiency of modified biochar. 2+ and 150mg / L Cd 2+ The initial pH values of the solutions were 4.83 and 5.75, respectively. The adsorption efficiency of 5-MgO-PBC was better in the pH range of 4 to 6, so the initial pH value of the heavy metal solution was selected for subsequent research.
[0062] 3.2 Effect of biochar dosage on biochar adsorption efficiency According to the results of the study on the effect of initial pH value, the Cu 2+ / Cd 2+ The solution was at the optimal pH value. Different dosages (0.125 g / L, 0.25 g / L, 0.5 g / L, 1 g / L, and 2 g / L) of biochar were placed in 150 mL conical flasks. Three replicates were set for each dosage. 25 mL of 60 mg / L Cu 2+ The operating conditions were: room temperature, shaking speed 200 rpm, and adsorption reaction lasted for 10 h. The same adsorption conditions were used to adsorb Cd 2+ The difference is that Cd 2+ The concentration of the solution is 150 mg / L.
[0063] There are many key factors that affect the efficiency of biochar in adsorbing heavy metals Cu(Ⅱ) / Cd(Ⅱ) in water, and the amount of biochar added is one of them. In the present embodiment, by adding modified biochar with different dosages, the adsorption efficiency of 5-MgO-PBC on Cu(Ⅱ) / Cd(Ⅱ) changes with the dosage. Figure 5 As shown in the figure, the dosage of 5-MgO-PBC has an effect on Cu 2+ (a) Cd 2+(b) Effect of adsorption amount and adsorption rate. The adsorption efficiency of Cu(Ⅱ) / Cd(Ⅱ) for both 60BC and 5-MgO-PBC increased with the increase of dosage. When the dosage of 5-MgO-PBC increased from 0.125g / L to 0.5g / L, the adsorption rate of Cu(Ⅱ) increased from 22.39% to 65.89%, and the adsorption rate of Cd(Ⅱ) increased from 21.05% to 69.05%. The efficiency of 60BC adsorption of Cu(Ⅱ) / Cd(Ⅱ) was 70.28% and 63.87% when the dosage was increased to 2g / L. When the dosage of 5-MgO-PBC was increased to 1g / L, the adsorption efficiency of Cu(Ⅱ) / Cd(Ⅱ) was as high as 99.37%; the adsorption rate did not show significant changes when the dosage continued to increase. The change of adsorption amount with dosage is quite different from the adsorption rate. When the dosage of 5-MgO-PBC increases from 0.125g / L to 0.5g / L, the adsorption amount of Cu(Ⅱ) decreases from 102.063mg / g to 82.523mg / g, and the adsorption amount of Cd(Ⅱ) decreases from 246.719mg / g to 207.135mg / g. When the dosage is 2g / L, the adsorption amount of Cu(Ⅱ) decreases to 30.736mg / g, and the adsorption amount of Cd(Ⅱ) decreases to 75mg / g.
[0064] In the present invention, the adsorption amount of 5-MgO-PBC for Cu(Ⅱ) / Cd(Ⅱ) is inversely proportional to the dosage, and the adsorption rate is proportional to the dosage. The trend of the adsorption amount and adsorption rate of 60BC changing with the dosage is also verified. The lower the dosage of 5-MgO-PBC, the lower the adsorption rate of Cu(Ⅱ) / Cd(Ⅱ). The reason is that the adsorption sites of the modified biochar are less and can be quickly saturated during the adsorption process. When the dosage of 5-MgO-PBC begins to increase, the adsorption sites in the system for adsorbing heavy metal ions increase accordingly, and the adsorption sites on the surface of 5-MgO-PBC are more sensitive to Cu 2+ 、Cd 2+ The difficulty of capturing is also reduced. This is also limited. Figure 5 It can be seen that if the dosage of 5-MgO-PBC is further increased, there is no significant change in the adsorption rate of Cu(Ⅱ) or Cd(Ⅱ). This phenomenon is attributed to the relationship between the concentration of heavy metal ions and the adsorption sites. 2+ 、Cd 2+ The concentration of Cu is limited. At the dosage of 1g / L, the concentration of Cu 2+ 、Cd 2+The removal rate has reached a constant value as the dosage of 5-MgO-PBC continues to increase. The reason why the adsorption amount of Cu(Ⅱ) / Cd(Ⅱ) per unit mass of 5-MgO-PBC decreases with the increase of dosage is that the concentration of heavy metal ions in the adsorption system is limited. The continuous addition of 5-MgO-PBC leads to an increase in the number of idle adsorption sites, and the ratio of effectively saturated adsorption sites to idle adsorption sites decreases, resulting in a decrease in the adsorption amount of 5-MgO-PBC.
[0065] Therefore, when the dosage of 5-MgO-PBC is 1g / L, the adsorption of Cu(Ⅱ) / Cd(Ⅱ) has achieved good results. From the perspective of economy and effectiveness, the adsorption effect is better when the dosage of 5-MgO-PBC is 1g / L and the adsorption time is 10h or more.
[0066] 3.3 Adsorption kinetics analysis The optimal values of these two parameters were determined based on the research results on the effects of initial pH value and biochar dosage. 2 + / Cd 2+ The solution was at the optimal pH value, the optimal amount of biochar was weighed into a 150 mL conical flask, and 25 mL of 60 mg / L Cu 2+ Solution, operating conditions: room temperature, shaking speed 200rpm, adsorption reaction lasts 24h, sampling time points are set at 0.5h, 1h, 2h, 4h, 6h, 8h, 10h, 12h, 24h, and three parallels are set for each level. The same adsorption conditions are used for adsorption of Cd 2+ The difference is that Cd 2+ The concentration of the solution is 150 mg / L.
[0067] In order to better understand the adsorption process of 60BC and 5-MgO-PBC on Cu(Ⅱ) / Cd(Ⅱ), the adsorption kinetics of 60BC and 5-MgO-PBC on Cu(Ⅱ) / Cd(Ⅱ) were evaluated. Figure 6As shown in (a) and (b), the removal rate of 60BC for 60 mg / L Cu(Ⅱ) at 24h adsorption equilibrium was only 41.97%; the removal rate of 150 mg / L Cd(Ⅱ) at 24h adsorption equilibrium was only 42.30%; the adsorption effect on Cu(Ⅱ) / Cd(Ⅱ) was poor. However, 5-MgO-PBC had a better adsorption performance for Cu(Ⅱ) / Cd(Ⅱ), and the adsorption equilibrium was achieved within 10h at the fastest, with adsorption efficiencies of 98.63% and 98.42%. The adsorption kinetics results showed that due to the interaction on the external surface, the adsorption of Cd(Ⅱ) by 5-MgO-PBC was much faster than that of Cu(Ⅱ) in the initial stage. Cu(Ⅱ) / Cd(Ⅱ) was rapidly adsorbed by 5-MgO-PBC by more than 70% within 4h, and then the adsorption rate gradually slowed down, reaching adsorption equilibrium at 10h (because there was no significant difference in adsorption capacity between 10h and 24h). The initial adsorption rate of 5-MgO-PBC was fast, which was due to the large number of unsaturated adsorption sites on the surface of biochar and strong ion exchange and electrostatic attraction at the initial stage of adsorption. The adsorption slowly reached equilibrium at about 10 hours, which may be due to the fact that the idle adsorption sites on the biochar gradually tended to saturation.
[0068] The adsorption data were fitted with pseudo-first-order kinetic (PFO) model and pseudo-second-order kinetic (PSO) model to analyze the adsorption kinetics of 5-MgO-PBC on Cu(Ⅱ) / Cd(Ⅱ). According to the fitting results, the PFO model determination coefficient (R 2 ) is small, and the equilibrium adsorption amount is quite different from the actual value, indicating that the PFO model cannot well describe the adsorption process of these two heavy metal ions. The PSO model can better describe the adsorption process of 5-MgO-PBC on Cu(Ⅱ) / Cd(Ⅱ), R 2 Value>0.99 (Cu:R 2 =0.996, Cd:R 2 =0.997), the q obtained by fitting e Value (Cu:q e =63.49mg / g; Cd:q e =150.55mg / g) is closer to the actual value measured in the study (Cu:q e =61.49mg / g; Cd:q e=147.64mg / g). The PFO model believes that the number of adsorption sites occupied by the adsorbent is proportional to the number of unoccupied adsorption sites. The PSO model shows that the adsorption rate of the adsorbent to the adsorbate is controlled by electron sharing and chemical adsorption on the heterogeneous surface of the adsorbent, respectively. The model can explain the adsorption processes of surface adsorption, liquid film diffusion and intraparticle diffusion, and can fully and accurately feedback the adsorption of Cu(Ⅱ) / Cd(Ⅱ) on 5-MgO-PBC. The research results show that the adsorption of Cu(Ⅱ) / Cd(Ⅱ) by phosphate-modified and metal oxide-modified biochar materials also conforms to the PSO model. The analysis results show that the unoccupied adsorption sites on the surface of 5-MgO-PBC are proportional to the adsorption rate, and chemical adsorption controls the entire rate-limiting step in its adsorption process of Cu(Ⅱ) / Cd(Ⅱ). Therefore, it is judged that the reason for the long adsorption equilibrium time in the whole process is that the adsorption of Cu(Ⅱ) / Cd(Ⅱ) by 5-MgO-PBC is mainly completed by chemical action.
[0069] 3.4. Adsorption isotherm analysis The optimal amount of biochar was weighed into a 150 mL conical flask, and the concentration gradient of Cu was 20 mg / L, 60 mg / L, 120 mg / L, 200 mg / L, 260 mg / L, and 300 mg / L. 2+ Solution (Cd 2+ Solution is 20mg / L, 60mg / L, 150mg / L, 200mg / L, 300mg / L, 400mg / L), adjust Cu 2+ / Cd 2+ The solution has the optimal pH value. Add 25mL of the above different concentrations of Cu 2+ The solution was set up in three parallels at each level, and the shaking speed was 200 rpm at 25 ° C for 10 h. The same adsorption conditions were used to adsorb Cd 2+ .
[0070] In order to evaluate the potential adsorption efficiency of 60BC and 5-MgO-PBC, the Langmuir and Freundlich models were used to fit the data of Cu(Ⅱ) / Cd(Ⅱ) adsorption on 60BC and 5-MgO-PBC, as shown in Figure 2. Figure 7 The Langmuir model assumes that the adsorbent surface is uniform and there is no interaction between the adsorbed molecules; the Freundlich model describes the adsorption on a heterogeneous surface without a theoretical maximum adsorption capacity. The data R of Cu(Ⅱ) adsorption on 60BC and 5-MgO-PBC were fitted according to the Langmuir model. 2 The values were as high as 0.9963 and 0.9988, and the Langmuir model fitted the data of Cd(Ⅱ) adsorption R 2The values were as high as 0.9984 and 0.9993; the Freundlich model fitted the R 2 Only 0.9483 and 0.8892, R 2 Only 0.9450 and 0.9361. Therefore, the Langmuir model can better describe the adsorption of Cu(Ⅱ) / Cd(Ⅱ) by 60BC and 5-MgO-PBC compared with the Freundlich model. This result can be explained by the fact that the large number of functional groups on the surface of 5-MgO-PBC can enhance its adsorption of heavy metal ions in the system. And in the whole adsorption process, the adsorption amount of Cu(Ⅱ) and Cd(Ⅱ) by 60BC and 5-MgO-PBC increases with the increase of initial concentration, and then gradually tends to equilibrium. This is mainly due to the fact that there are enough free adsorption sites and groups on the surface of the adsorbent at the beginning of adsorption, and there is less competitive adsorption between heavy metal ions. As the adsorption process proceeds, the adsorption sites are gradually saturated, the surface functional groups are reduced, and the adsorption competition intensifies, leading to adsorption equilibrium.
[0071] The Langmuir model can describe the adsorption of Cu(Ⅱ) / Cd(Ⅱ) by 60BC and 5-MgO-PBC relatively well, proving that this adsorption behavior belongs to monolayer adsorption. The fitting results show that the maximum theoretical adsorption capacity of 60BC for Cu(Ⅱ) / Cd(Ⅱ) is 57.33 mg / g and 87.26 mg / g, and the maximum theoretical adsorption capacity of 5-MgO-PBC for Cu(Ⅱ) / Cd(Ⅱ) is 190.74 mg / g and 284.50 mg / g, which is 3.2 to 3.3 times that of 60BC. The phosphate / magnesium oxide composite modified biochar of the embodiment of the present invention has a high adsorption capacity for Cu(Ⅱ) / Cd(Ⅱ), and 5-MgO-PBC is considered to be a very promising modified biochar for removing Cu(Ⅱ) / Cd(Ⅱ) from water.
[0072] 3.5 Effects of coexisting ions and ionic strength on biochar adsorption efficiency Ionic strength studies were based on Na + As background ions, 6 mg / LCu was prepared with different concentrations of NaNO3 solution as solvent. 2+ Solution and 150mg / L Cd 2+ Solution. The NaNO3 solution with concentrations of 0.01mol / L, 0.25mol / L, and 1.0mol / L constitutes a complete solvent system. Pipette 25mL Cu 2+ or Cd 2+ The solution was placed in a 150 mL conical flask, the solution was adjusted to the optimal pH value, the optimal amount of biochar was weighed and added to the conical flask; operating conditions: room temperature, shaking speed 200 rpm, constant temperature shaking for 10 hours. Three parallels were set for each level.
[0073] The study of coexisting ions selected K + and Ca 2+ As the coexisting cations of Cu(Ⅱ) / Cd(Ⅱ) solution, the effects of different types and concentrations (0.01mol / L, 0.25mol / L and 1mol / L) of interfering ions on the adsorption efficiency of Cu(Ⅱ) / Cd(Ⅱ) by biochar were investigated. 2+ or 150mg / L Cd 2+ KNO3, Ca(NO3)2 solution, adjust the solution to the optimal pH value, take the optimal amount of biochar in a 150mL conical flask, add 25mL Cu 2+ Solution or Cd 2+ Solution, operating conditions: room temperature, shaking speed 200rpm, adsorption reaction lasts 10h. Three parallels are set for each level.
[0074] There are usually other cations in industrial wastewater and natural water, which may occupy the active adsorption sites of biochar and interfere with the biochar's absorption of Cu. 2+ and Cd 2+ In order to evaluate the feasibility of 5-MgO-PBC in actual wastewater treatment, the adsorption of K + 、Na + , Ca 2+ Ionic strength and its adsorption of Cu 2+ and Cd 2+ The impact of Figure 8 and Fig. 9 As shown. Figure 8 It can be seen that K + 、Na + , Ca 2+ Any of the above has an effect on the adsorption of Cu on 5-MgO-PBC. 2+ The efficiency of 5-MgO-PBC adsorption was not significantly affected, even at ion concentrations as high as 1 mol / L. The ionic forms of K, Na, and Ca will not be hydrolyzed or precipitated in this adsorption system, and the ionic sizes of these cations are relatively large, which will not affect the occurrence of ion exchange. 2+ , different K + The adsorption amounts at the concentrations were 148.48 mg / g, 148.35 mg / g and 147.99 mg / g, respectively, which was 98.77% of that in the absence of coexisting cations, indicating that K + Adsorption of Cd on 5-MgO-PBC 2+ At the same time, the Na+ Under the interference, 5-MgO-PBC has a great influence on Cd 2+ The adsorption amount of Ca2+ varied between 148.72 and 149.70 mg / g, with an overall variation of about 1%, and did not decrease significantly compared with the adsorption amount when there was no coexisting cation. 2+ When the concentration is 0.01mol / L, 5-MgO-PBC has a significant effect on Cd 2+ The adsorption capacity was 145.75 mg / g, and the adsorption capacity did not change much; when the concentration increased from 0.25 mol / L to 1.0 mol / L, the adsorption capacity decreased from 144.49 mg / g to 141.26 mg / g, a decrease of 5.7%. The reason for the decrease in adsorption capacity may be Ca 2+ and Cd 2+ The charge properties of 5-MgO-PBC are similar. In the coexistence system of Ca and Cd ions at high concentrations, competitive adsorption occurs on the surface of the material, causing the adsorption amount to decrease by 5.7%. + 、Na + , Ca 2+ Adsorption of Cu on 5-MgO-PBC 2+ and Cd 2+ There was no obvious inhibitory effect during the process, indicating that the ionic strength had an important effect on the adsorption of Cu by 5-MgO-PBC. 2+ and Cd 2+ The influence is small. If the adsorbent is affected by the ionic strength during the adsorption process, it means that the coordination between the adsorbent and the solute belongs to the outer orbital coordination. The inner orbital coordination is not affected by the ionic strength, which indirectly proves that the inner orbital complex can be formed between 5-MgO-PBC and Cu(Ⅱ) / Cd(Ⅱ), and also indicates that the adsorption process belongs to chemical adsorption.
[0075] 3.6 Cyclic desorption analysis The modified biochar used to study the adsorption kinetics was collected and filtered, and dried in an oven at 85°C for 6 hours. Then, 1 g of the dried sample was mixed with 1000 mL of 0.1 mol / L NaOH solution and desorbed for 24 hours at a shaking speed of 200 rpm. The desorbed modified biochar was filtered and washed with ultrapure water until neutral, and then dried in an oven for 12 hours. The dried modified biochar was placed in a conical flask and Cu 2+ Solution (60mg / L) or Cd 2+ Solution (150 mg / L), room temperature, shaker speed 200 rpm, constant temperature shaking for 10 hours. Three parallels were set for each level. Four cycles of adsorption and desorption were performed under the same conditions to verify the regeneration (cyclic adsorption) efficiency of the modified biochar.
[0076] Although the modified biochar has a good adsorption effect on Cu(Ⅱ) / Cd(Ⅱ) in the entire adsorption system, the adsorption material is cyclic in practical applications. One-time use not only increases the treatment cost of heavy metal-contaminated wastewater, but also causes secondary pollution if the treated adsorption material is not properly disposed. Therefore, the regeneration performance of 5-MgO-PBC has become an important indicator for evaluating its use time. The study of the cyclic desorption of adsorption materials, i.e., the regeneration performance, generally uses a desorption solution (extract solution) to desorb pollutants from the adsorption material and restore the adsorption efficiency of the material. The modified biochar after adsorption is desorbed by 0.1M NaOH solution and then recycled, which can effectively reduce economic and energy losses.
[0077] The cyclic adsorption capacity of 5-MgO-PBC is as follows Fig.10 As shown in the figure, after the second cycle, the adsorption of Cu(Ⅱ) / Cd(Ⅱ) by 5-MgO-PBC was 98.61% and 96.80% of the initial adsorption, corresponding to 60.43 mg / g and 143.88 mg / g, respectively. Although some adsorption sites and functional groups can be restored by elution and regeneration with NaOH, the changes in the structure of the modified biochar may make it difficult to regenerate the adsorption sites, resulting in a significant decrease in the adsorption after 3 to 5 cycles. Finally, after five cycles, the adsorption of Cu(Ⅱ) / Cd(Ⅱ) by 5-MgO-PBC can still reach 76.55% and 72.89% of the initial adsorption, corresponding to 46.91 mg / g and 108.35 mg / g, respectively. After five cycles, the adsorption rate of 5-MgO-PBC for Cu(Ⅱ) / Cd(Ⅱ) decreased by about 20%. This result may be caused by the partial loss of magnesium oxide in 5-MgO-PBC, the partial loss of adsorption sites, and the subtle changes in the material structure and pore blockage during the regeneration process.
[0078] 3.7. The static adsorption efficiency of heavy metals Cu(Ⅱ) / Cd(Ⅱ) by 5-MgO-PBC was studied by single factors such as the initial pH value of the solution, the strength of coexisting ions and the amount of biochar added. The fitting results of the adsorption kinetics and adsorption isotherm model for the static adsorption of Cu(Ⅱ) / Cd(Ⅱ) by 5-MgO-PBC were analyzed.
[0079] (1) The adsorption results of different initial pH values of the solution showed that the phosphate / magnesium oxide composite modified 5-MgO-PBC had a strong buffering capacity for the adsorption of Cu(Ⅱ) / Cd(Ⅱ) in water. That is, when the initial pH of the solution was ≥3, 5-MgO-PBC had a strong buffering capacity for the adsorption of 60 mg / LCu. 2+ and 150mg / L Cd 2+The removal rate can reach 90% or above. The results of the study on the dosage of modified biochar showed that when the dosage was 1g / L, the adsorption rate of Cu(Ⅱ) / Cd(Ⅱ) was as high as 99.37%, which was in line with the limit values of enterprise wastewater discharge under the current standards (the total copper concentration limit was 0.5mg / L and the total cadmium concentration limit was 0.1mg / L).
[0080] (2) The adsorption kinetics and isotherms of heavy metals Cu(Ⅱ) / Cd(Ⅱ) in water by 5-MgO-PBC showed that the adsorption process conformed to the pseudo-second-order kinetic model and the Langmuir model, which means that the adsorption and removal of Cu(Ⅱ) / Cd(Ⅱ) was mainly chemical adsorption. According to the fitting calculation, the theoretical maximum adsorption capacity of Cu(Ⅱ) / Cd(Ⅱ) was 190.74 mg / g and 284.50 mg / g, respectively, which was 3.2 to 3.3 times that of the original biochar (60BC).
[0081] (3) Under the interference of different concentrations of inorganic cations, the adsorption efficiency of 5-MgO-PBC for Cu(Ⅱ) / Cd(Ⅱ) was not significantly affected. Through cyclic adsorption and desorption studies, it was found that the efficiency of 5-MgO-PBC for adsorbing Cu(Ⅱ) / Cd(Ⅱ) decreased by about 20% after 5 cycles. This may be due to the partial loss of magnesium oxide in 5-MgO-PBC, the partial loss of adsorption sites, the slight change of structure, and the blockage of pores during the regeneration process.
[0082] 4. Mechanism of Cu(Ⅱ) / Cd(Ⅱ) adsorption on MgO-PBC 4.1 Surface morphology analysis Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) were used to analyze the surface morphology and elemental composition of biochar materials before and after adsorption of Cu(Ⅱ) / Cd(Ⅱ). The analysis results are shown in Figure 2. Fig.11 As shown in the figure, it can be seen that the surface of 60BC is a porous structure, the pores are mostly micro-mesoporous and the surface is relatively smooth. After phosphate / magnesium oxide composite modification, 5-MgO-PBC softens the biomass due to phosphate activation. After co-pyrolysis, the pores become medium- and macro-porous structures, and the pore channels are destroyed and blocked, and the surface becomes rough. Fig.11 (b) Figure and EDS spectrum show that some pore channels of 5-MgO-PBC are blocked by nano-spherical MgO particles and some irregular particles brought by phosphate modification, indicating that MgO and P are successfully loaded on biochar.
[0083] The SEM images and EDS spectra of 5-MgO-PBC after adsorption of Cu(Ⅱ) are shown in Figure 2. Fig.11As shown in (c) and (d), after adsorption, Cu compounds (including precipitation, complexation, etc.) are attached to the surface and pores of 5-MgO-PBC. The precipitated particles are small and have no fixed shape, and the precipitation is flocculent. The EDS spectrum shows that the content of Cu in the modified biochar after adsorption is 12.7% (Wt%), ranking third, while the contents of Mg and P are much reduced, proving that Cu(Ⅱ) is successfully adsorbed by 5-MgO-PBC. Fig.11 (e) and (f) are the SEM images and EDS spectra of 5-MgO-PBC after adsorbing Cd(Ⅱ). From the morphological point of view, many blocky particles appear on the surface of 5-MgO-PBC after adsorbing Cd. The Cd content in the EDS spectrum is as high as 8.9% (Wt%), which also illustrates the effective adsorption of Cd(Ⅱ) by 5-MgO-PBC.
[0084] 4.2 Specific surface area analysis The BET test was performed on 5-MgO-PBC to analyze its specific surface area and pore size. The N2 adsorption-desorption isotherm was as follows: Fig.12 As shown in the test results, the specific surface area of 5-MgO-PBC is 199.67m 2 / g, pore volume 0.80cm 3 / g, and the average pore size is 4.46nm. The N2 adsorption-desorption isotherm is a typical IV isotherm with a hysteresis loop, indicating that 5-MgO-PBC has a medium- and large-pore structure. The large specific surface area contains abundant adsorption sites, which can improve the adsorption capacity of modified biochar to a certain extent. However, the specific surface area of the modified 5-MgO-PBC is only 199.67m 2 / g, which corresponds to the pores of the above-mentioned 5-MgO-PBC being blocked by the load. It also shows that the adsorption capacity of biochar is affected by many factors besides specific surface area.
[0085] 4.3 Surface functional group analysis In order to further confirm the surface properties of modified biochar and the changes in its surface functional groups and vibration peaks before and after adsorption, the surface functional groups of 5-MgO-PBC before and after adsorption of Cu(Ⅱ) / Cd(Ⅱ) were analyzed by Fourier transform infrared spectrometer (FT-IR) and compared with 60BC. The infrared spectra are shown in Figure 2. Fig.13 As shown in the figure, it can be seen that the surface of 60BC has a variety of functional groups, but after phosphate / magnesium oxide composite modification, the vibration peaks of some original functional groups gradually weakened. In the FT-IR spectra of 60BC and 5-MgO-PBC, 3434cm −1 The band is attributed to the hydroxyl (-OH) vibration peak. The decrease in -OH intensity after modification can be attributed to the peak at 576 cm −1 The introduction of metal-oxygen bonds (Mg-O) at 1600cm−1 The peaks near the 5-MgO-PBC belong to the stretching vibration of -COOH, which is more obvious on 5-MgO-PBC than on 60BC, indicating that the phosphate / magnesium oxide composite modification can increase the number of oxygen-containing groups on the biochar surface. After 5-MgO-PBC adsorbs Cu(Ⅱ) / Cd(Ⅱ), the Mg-O bond shifts from 576cm −1 Transformed to 616cm −1 , which may be the reason for the formation of HMs-O bond. −1 and 1050cm −1 The peak is attributed to phosphate (PO4 3- ), proving the existence of KH2PO4 calcination products. 576cm −1 and 876cm −1 The vibration peaks at PO4 can be attributed to magnesium oxide (Mg-O) and magnesium oxyphosphate (PO-Mg), indicating that magnesium oxide was successfully loaded on 5-MgO-PBC. 3- It can react with metal ions to form metal-phosphate precipitates. The FT-IR spectrum of 5-MgO-PBC after adsorption of Cu(Ⅱ) / Cd(Ⅱ) confirmed this result, such as Fig.13 As shown, PO4 3- Group (961cm −1 and 1050cm −1 ) vibration peak in the adsorption of Cu 2+ and Cd 2+ In addition, the vibration peak of -OH after the metal cations complete the specific adsorption is located at 3600cm −1 Nearby offset.
[0086] 4.4 Crystal structure analysis The XRD patterns of 5-MgO-PBC before and after adsorption of heavy metals Cu(Ⅱ) / Cd(Ⅱ) are shown in Figure 2. Fig.14As shown, 5-MgO-PBC mainly contains 2-3 crystal phases before adsorption. The characteristic diffraction peaks at 2θ=36.9°, 42.9°, 62.2°, and 74.6° correspond to the (111), (200), (220), and (311) crystal planes of MgO crystals, and the characteristic diffraction peak at 2θ=18.56° corresponds to the (001) crystal plane of Mg(OH)2. The diffraction peaks at 2θ=31.5°, 45.2°, 56.1°, 28.6°, 20.9°, and 40.8° belong to Mg2P2O7, Mg3P2, MgP4, and P2O5. After the adsorption of Cu(Ⅱ), the characteristic peaks of MgO and other substances on 5-MgO-PBC disappeared, and the main diffraction peaks 2θ=16.7°, 30.4°, 28.2°, and 32.9° were consistent with Cu(OH)2, CuCO3, Cu2(CO3)2(OH)2, and Cu3(PO4)2, which contain basic copper carbonate and other types of precipitates.
[0087] After 5-MgO-PBC adsorbed Cd(Ⅱ), the characteristic peaks of MgO and other substances also disappeared. The main characteristic diffraction peaks 2θ=30.9°, 23.7°, 34.7°, 17.6°, and 60.4° were highly consistent with the peaks of Cd5(PO4)3OH, CdCO3, Cd3(PO4)2, Cd(OH)2, and Cd5(PO4)3Cl, indicating that precipitates of CdCO3, Cd3(PO4)2, etc. were formed as the main substances during the adsorption process.
[0088] 4.5 Chemical bond analysis The content and existence form of the surface elements of 5-MgO-PBC were analyzed by X-ray photoelectron spectroscopy. Fig.15 , Fig.16 and Fig.17 shown.
[0089] In the general spectrum of 5-MgO-PBC ( Fig.15 As shown in the figure), the P 2p peak appears at 133eV, the Mg 1s peak appears at 1310eV, and the Auger peak of Mg appears at 307eV and 351eV. The appearance of these characteristic peaks indicates that MgO and P are successfully loaded on the biochar, and verifies the characterization results of FT-IR. The peak intensity of Mg is weakened to varying degrees after the adsorption of Cu(Ⅱ) / Cd(Ⅱ), indicating that a part of the Mg ions on 5-MgO-PBC are lost during the adsorption process, and ion exchange occurs with Cu(Ⅱ) / Cd(Ⅱ), which is also confirmed by the reduction of Mg element in the EDS energy spectrum after adsorption. After the adsorption, the total spectrum Fig.15 The 2p peak of Cu was found at a binding energy of 933.2 eV, proving the adsorption of Cu(Ⅱ) by 5-MgO-PBC. Fig.16(a) is the C 1s spectrum before adsorption, the main functional groups are C=O (287 eV), C-OH (286 eV), CC (285 eV) and C=C (284.6 eV); Fig.16 As shown in (b), the intensity of CC and C=C did not change after the adsorption of Cu(Ⅱ), the intensity of C-OH decreased, and the peak of C=O did not appear, which indicates that both carboxyl and hydroxyl groups participated in the adsorption of Cu(Ⅱ), and hydroxyl groups can be complexed with Cu(Ⅱ). By observing the changes before and after P 2p adsorption, it was found that the intensity of metaphosphate was greatly reduced, indicating that metaphosphate and Cu(Ⅱ) underwent chelation reaction; the intensity of phosphate and pyrophosphate did not change, proving that they did not participate in the adsorption of Cu(Ⅱ). Combined with the XRD results, the products produced when 5-MgO-PBC adsorbed Cu(Ⅱ) included basic copper carbonate precipitation, copper phosphate chelate and other substances.
[0090] like Fig.15 As shown in the figure, after the adsorption of Cd (Ⅱ), the peak intensities of Mg 1s and Mg Auger peaks weakened more significantly, and characteristic peaks of Cd appeared at binding energies of 406.5eV, 618.5eV, and 652.4eV, proving that Mg plays an important role in the adsorption of Cd (Ⅱ). Fig.17 In the results, the intensity of CC and C=C did not change significantly before and after the adsorption of Cd (Ⅱ), the peak intensity of C=O showed the same trend as the change of C 1s when Cu (Ⅱ) was adsorbed, and the intensity of C-OH decreased, indicating that carboxyl and hydroxyl groups participated in the adsorption of Cd (Ⅱ). Fig.17 (c) and (d) show that the intensity of metaphosphate, phosphate and pyrophosphate in P 2p decreased after adsorption, proving that precipitation and complexation occurred during the adsorption process while chelation occurred. Combined with the results of XRD, the products produced when Cd(Ⅱ) was adsorbed mainly included cadmium hydroxide, cadmium carbonate precipitation and cadmium hydroxyphosphate.
[0091] 4.6 Adsorption mechanism The functional groups on the surface of biochar will affect its adsorption capacity for heavy metal ions. Studies have shown that the surface functional groups of biochar can undergo electrostatic attraction, ion exchange or surface complexation with heavy metal ions. Fig.13 The FT-IR spectrum shows that there are Mg-O and PO4 on the surface of 5-MgO-PBC 3- The characteristic peaks of polar groups such as PO-Mg and PO-Mg, the peak intensities of these three groups decreased after the adsorption of Cu(Ⅱ) / Cd(Ⅱ), and the Mg in the solution after adsorption 2+ The concentration of MgO-PBC increases and the EDS spectrum after adsorption confirms that the Mg content of 5-MgO-PBC decreases, proving that Mg exists on the surface of 5-MgO-PBC during the adsorption process.2+ With Cu in solution 2 + and Cd 2+ An ion exchange reaction occurs, and precipitates such as Cu(OH)2, Cu3(PO4)2, Cd(OH)2 and Cd3(PO4)2 are produced after the reaction.
[0092] Cu(OH)2 and Cd(OH)2 have a certain solubility in the solution, but the XRD results show that the final products after Cu(Ⅱ) / Cd(Ⅱ) adsorption are basic copper carbonate, copper carbonate and cadmium carbonate precipitation. The multivariate analysis shows that the functional groups on the surface of biochar are important for providing heavy metal ions (such as Cu 2+ and Cd 2+ ) binding sites are of great significance. Generally speaking, the more oxygen-containing functional groups on the surface of biochar, the stronger the adsorption capacity of biochar for heavy metal ions. Combined with the XPS analysis results, it is known that the intensity of C=O and C-OH decreased significantly after adsorption, indicating that oxygen-containing functional groups may provide CO3 for the conversion of heavy metal ions into precipitation during the adsorption process. 2- Therefore, precipitation is also one of the mechanisms of 5-MgO-PBC adsorbing Cu(Ⅱ) / Cd(Ⅱ).
[0093] On the one hand, the FT-IR and XPS results verified the existence of polar groups on the surface of biochar, which can interact with Cd(Ⅱ) through surface complexation to generate Cd5(PO4)3OH and Cd5(PO4)3Cl complexes. On the other hand, there are some excitation peaks of heterocyclic aromatic compounds in the FT-IR spectrum, which can act as π electrons, Cd 2+ It is electron-deficient. The π electrons of heterocyclic aromatic compounds can provide electrons to Cd 2+ Complexation improves the adsorption efficiency of 5-MgO-PBC, so the complexation of Cd-π bond may be one of the mechanisms of 5-MgO-PBC adsorption of Cd(Ⅱ). The adsorption mechanism of Cu(Ⅱ) and Cd(Ⅱ) by 5-MgO-PBC mainly involves ion exchange, surface coprecipitation and complexation, and electrostatic attraction may be involved in the entire adsorption process.
[0094] 4.7. In the present invention, 5-MgO-PBC was characterized and analyzed by various methods such as BET, SEM-EDS, FT-IR, XRD and XPS. The fitting results of the adsorption kinetics and adsorption isotherm model of 5-MgO-PBC adsorbing Cu(Ⅱ) / Cd(Ⅱ) were combined to analyze the possible mechanism of 5-MgO-PBC adsorbing heavy metals Cu(Ⅱ) / Cd(Ⅱ). The results are as follows: (1) 5-MgO-PBC was characterized and analyzed using a variety of methods such as SEM-EDS, FT-IR, XRD and XPS. It was found that 5-MgO-PBC exhibited a rich porous structure, and P and MgO were successfully loaded on the surface and in the pores of the material.
[0095] (2) Surface coprecipitation and ion exchange are the main mechanisms for the adsorption of Cu(Ⅱ) by 5-MgO-PBC. Oxygen-containing functional groups can provide carbonate for some precipitation reactions. The main substances produced by surface coprecipitation are copper hydroxide, copper phosphate and basic copper carbonate. The main mechanisms for the adsorption of Cd(Ⅱ) by 5-MgO-PBC are ion exchange, surface coprecipitation and complexation. Electrostatic attraction may also be one of the mechanisms for the adsorption of Cu(Ⅱ) and Cd(Ⅱ) by 5-MgO-PBC.
[0096] 5. Dynamic adsorption efficiency of Cu(Ⅱ) / Cd(Ⅱ) on MgO-PBC The embodiment of the present invention studies the dynamic adsorption efficiency of 5-MgO-PBC for heavy metals Cu(Ⅱ) / Cd(Ⅱ) by changing the bed height, influent flow rate and influent concentration, and uses the BDST model, Thomas model and Wolborska model to describe and predict the process of dynamic adsorption of Cu(Ⅱ) / Cd(Ⅱ) by 5-MgO-PBC.
[0097] (1) The dynamic adsorption of Cu(Ⅱ) / Cd(Ⅱ) by 5-MgO-PBC is affected to varying degrees by the bed height, influent flow rate and influent concentration. The breakthrough time and saturation time increase with the increase of bed height, and the adsorption amount increases with the increase of bed height and influent concentration. The dynamic adsorption efficiency of 5-MgO-PBC can be improved by reducing the influent flow rate, increasing the bed height and increasing the influent concentration.
[0098] (2) Through intuitive analysis of the dynamic adsorption data, when the bed height is 7 cm, the inlet flow rate is 20 mL / min, and the inlet Cu(Ⅱ) concentration is 60 mg / L, the dynamic adsorption capacity of 5-MgO-PBC for Cu(Ⅱ) can reach 78.87 mg / g; when the bed height is 5 cm, the inlet flow rate is 20 mL / min, and the inlet Cd(Ⅱ) concentration is 150 mg / L, the dynamic adsorption rate of 5-MgO-PBC for Cd(Ⅱ) is as high as 88.95%.
[0099] (3) The BDST model and the Thomas model can analyze and predict the entire dynamic adsorption system, fit the dynamic adsorption process of Cu(Ⅱ) / Cd(Ⅱ) on 5-MgO-PBC and draw the penetration curve. The Thomas model fits the R of the dynamic adsorption of Cu(Ⅱ) on 5-MgO-PBC. 2 The value is in the range of 0.967 to 0.994, and the fitting effect is good. The R2 The values are all greater than 0.99, and the difference between the theoretical adsorption amount and the actual adsorption amount is small, which provides strong data support for the actual industrial treatment of heavy metal contaminated wastewater with 5-MgO-PBC.
[0100] The above is only a specific implementation of the present invention, which enables those skilled in the art to understand or implement the present invention. Although detailed descriptions are given with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments, and they should all be covered by the protection scope of the claims.
Claims
1. A method for preparing phosphate / magnesium oxide composite modified biochar, characterized in that: The steps include: Step 1, preparation of phosphate-modified biochar: taking corn straw powder and placing it in potassium dihydrogen phosphate solution to form a P-impregnated biomass raw material; then drying the P-impregnated biomass raw material; placing the dried P-impregnated biomass raw material into a muffle furnace, evacuating the furnace, heating from room temperature to 800°C and maintaining a constant temperature for 2 hours; cooling to room temperature and taking out the sample for storage to obtain base biochar PBC; Step 2, preparation of phosphate / magnesium oxide composite modified biochar: take the base biochar PBC and add it to the MgCl2 solution and stir, then heat it to 85°C, then add Na2CO3 solution, heat it in a water bath to 85°C, then wash the resulting precursor until the pH is constant, and dry it; then put the dried precursor into the muffle furnace, evacuate it, and keep the temperature constant at 800°C from the starting temperature of room temperature for 2 hours; after cooling to room temperature, take out the sample for storage, and obtain modified biochar with PBC as the base material, named MgO-PBC.
2. The method for preparing a phosphate / magnesium oxide composite modified biochar according to claim 1, characterized in that: In step 1, the corn stalk powder is passed through 60 mesh.
3. The method for preparing a phosphate / magnesium oxide composite modified biochar according to claim 2, characterized in that: In step 1, the concentration of the potassium dihydrogen phosphate solution is 0.36 mol / L, and the 60-mesh corn straw powder and the potassium dihydrogen phosphate solution are mixed in a ratio of 1:10 (m:V), that is, each gram of 60-mesh corn straw powder is mixed with 10 mL of the potassium dihydrogen phosphate solution.
4. The method for preparing a phosphate / magnesium oxide composite modified biochar according to claim 3, characterized in that: In step 1, after mixing evenly, heat in a water bath at 85°C at 600 rpm for 6 h.
5. The method for preparing a phosphate / magnesium oxide composite modified biochar according to claim 4, characterized in that: In step 1, the drying temperature is 85°C and the time is 12 hours.
6. The method for preparing a phosphate / magnesium oxide composite modified biochar according to claim 1, characterized in that: In step 2, the mass ratio of base biochar PBC to Mg is 1:0.
24.
7. The method for preparing a phosphate / magnesium oxide composite modified biochar according to claim 6, characterized in that: In step 2, 5 g of base biochar PBC was added to 50 mL of 1.0 mol / L MgCl2 solution; 50 mL of 1.0 mol / L Na2CO3 solution was added; the drying temperature was 85°C and the time was 24 h; the modified biochar with PBC as the base material was named 5-MgO-PBC.
8. The method for preparing a phosphate / magnesium oxide composite modified biochar according to claim 7, characterized in that: In step 1 and step 2, the temperature is increased to 800° C. at a heating rate of 10° C. / min.
9. Use of the phosphate / magnesium oxide composite modified biochar prepared by the method of claims 1-8 in adsorbing heavy metal Cu / Cd contaminated wastewater.
10. Application of phosphate / magnesium oxide composite modified biochar prepared by the method according to claim 9 in adsorption of heavy metal Cu / Cd polluted wastewater, characterized in that: The initial pH of heavy metal Cu / Cd polluted wastewater is ≥3; the dosage of phosphate / magnesium oxide composite modified biochar is 1g / L, the adsorption time is more than 10h, and Cu 2+ The concentration is 5~100mg / L, Cd 2+ The concentration is 100-200 mg / L.